Comparison of three current sets of electrocardiographic interpretation criteria for use in screening athletes. Issue 5 (11th December 2014) - Riding, Nathan R; Sheikh, Nabeel; Adamuz, Carmen; Watt, Victoria; Farooq, Abdulaziz; Whyte, Gregory P; George, Keith P; Drezner, Jonathan A; Sharma, Sanjay; Wilson, Mathew G
Abstract : Background: An increasing number of sporting bodies report unacceptably high levels of false-positive ECGs when undertaking pre-participation cardiac screening. To address this issue, modified ECG interpretation criteria have become available for use within athletes. Objective: This study assessed the accuracy of the new 2014 'Refined Criteria' against the 2013 Seattle Criteria and the 2010 European Society of Cardiology (ESC) recommendations in a cohort of Arabic, black and Caucasian athletes. Methods: 2491 male athletes (1367 Arabic, 748 black and 376 Caucasian) undertook pre-participation screening including a 12-lead ECG, with further investigation(s) upon indication. Results: Ten athletes (0.4%) were identified with cardiac pathology; seven with hypertrophic cardiomyopathy (HCM; five black and two Arabic) and three Arabs with Wolff–Parkinson–White syndrome (WPW). All three ECG criteria were 100% sensitive identifying all cases of HCM and WPW. The 2014 Refined Criteria reduced (p<0.0001) the prevalence of an abnormal ECG to 5.3% vs 11.6% (Seattle Criteria) and 22.3% (2010 ESC recommendations). The 2014 Refined Criteria significantly (p<0.0001) improved specificity (94.0%) across all ethnicities compared with the Seattle Criteria (87.5%) and ESC recommendations (76.6%). Black athletes continue to present a higher prevalence (p<0.0001) of abnormal ECGs compared with Arabic and Caucasian athletes (10% vs 3.6% and 2.1%). Conclusions: The 2014 Refined Criteria for athlete ECG interpretation outperformed both the 2013 Seattle Criteria and the 2010 ESC recommendations by significantly reducing the number of false-positive ECGs in Arabic, black and Caucasian athletes while maintaining 100% sensitivity for serious cardiac pathologies.